Neuromuscular electrostimulation for adults with chronic obstructive pulmonary disease - Hill, Kylie; Cavalheri, Vinicius; Mathur, S.; Roig, M.; Janaudis-Ferreira, T.; Robles, P.; Dolmage, T.; Goldstein, R. (John Wiley & Sons, Ltd., 2018)
© 2018 The Cochrane Collaboration. Background: In people with chronic obstructive pulmonary disease (COPD), the use of neuromuscular electrostimulation (NMES) either alone, or together with conventional exercise training, might improve the condition of the peripheral muscles, increase exercise capacity and functional performance, reduce symptoms and improve health-related quality of life (HRQoL). Objectives: To determine the effects of NMES, applied in isolation or concurrently with conventional exercise training to one or more peripheral muscles, on peripheral muscle force and endurance, muscle size, exercise capacity, functional performance, symptoms, HRQoL and adverse events in people with COPD. Search methods: We searched the Cochrane Airways Group Specialised Register, the Physiotherapy Evidence Database, clinical trial registries and conference abstracts on 14 March 2018. Selection criteria: Randomised controlled trials that recruited adults with COPD if they had compared outcomes between a group that received NMES and a group that received usual care or compared outcomes between a group that received NMES plus conventional exercise training and a group that participated in conventional exercise training alone. Data collection and analysis: Two review authors independently extracted data and assessed risk of bias using the Cochrane 'Risk of bias' tool. We expressed continuous data as either the standardised mean difference (SMD) or mean difference (MD) with the corresponding 95% confidence interval (CI). We assessed the quality of evidence using the GRADE approach. Main results: Nineteen studies met the inclusion criteria of which 16 contributed data on 267 participants with COPD (mean age 56 to 76 years and 67% were men). Of these 16 studies, seven explored the effect of NMES versus usual care and nine explored the effect of NMES plus conventional exercise training versus conventional exercise training alone. Six studies utilised sham stimulation in the control group. When applied in isolation, NMES produced an increase in peripheral muscle force (SMD 0.34, 95% CI 0.02 to 0.65; low-quality evidence) and quadriceps endurance (SMD 1.36, 95% CI 0.59 to 2.12; low-quality evidence) but the effect on thigh muscle size was unclear (MD 0.25, 95% CI -0.11 to 0.61; low-quality evidence). There were increases in six-minute walk distance (6MWD) (MD 39.26 m, 95% CI 16.31 to 62.22; low-quality evidence) and time to symptom limitation exercising at a submaximal intensity (MD 3.62 minutes, 95% CI 2.33 to 4.91). There was a reduction in the severity of leg fatigue on completion of an exercise test (MD -1.12 units, 95% CI -1.81 to -0.43). The increase in peak rate of oxygen uptake (VO 2peak ) was of borderline significance (MD 0.10 L/minute, 95% CI 0.00 to 0.19). For NMES with conventional exercise training, there was an uncertain effect on peripheral muscle force (SMD 0.47, 95% CI -0.10 to 1.04; very low-quality evidence) and there were insufficient studies to undertake a meta-analysis on the effect on quadriceps endurance or thigh muscle size. However, there was an increase in 6MWD in favour of NMES combined with conventional exercise training (MD 25.87 m, 95% CI 1.06 to 50.69; very low-quality evidence). In people admitted to either in an intensive care unit or a respiratory high dependency centre, NMES combined with conventional exercise reduced the time taken for participants to first sit out of bed by 4.98 days (95% CI -8.55 to -1.41; very low-quality evidence), although the statistical heterogeneity for this analysis was high (I 2 = 60%). For both types of studies (i.e. NMES versus usual care and NMES with conventional exercise training versus conventional exercise training alone), there was no risk difference for mortality or minor adverse events in participants who received NMES. Authors' conclusions: NMES, when applied in isolation, increased quadriceps force and endurance, 6MWD and time to symptom limitation exercising at a submaximal intensity, and reduced the severity of leg fatigue on completion of exercise testing. It may increase VO 2peak , but the true effect on this outcome measure could be trivial. However, the quality of evidence was low or very low due to risk of bias within the studies, imprecision of the estimates, small number of studies and inconsistency between the studies. Although there were no additional gains in quadriceps force with NMES plus conventional exercise training, there was evidence of an increase in 6MWD. Further, in people who were the most debilitated, the addition of NMES may have accelerated the achievement of a functional milestone, that is, the first time someone sits out of bed.